2014
DOI: 10.4018/ijicte.2014040101
|View full text |Cite
|
Sign up to set email alerts
|

Socio-Psychological Dimensions of Mobile Phone Addiction and Usage Patterns amongst Teenagers in Higher Institutions of Learning in Kwara State

Abstract: Mobile phone addiction is now a common phenomenon in the 21st century, especially among teenagers due to the unusual cravings in the use of technological devices. In view of this phenomenon, the study examined the socio-psychological dimensions of mobile phone addiction and usage patterns amongst teenagers in three Higher Institutions of Learning in Kwara State, Nigeria. Descriptive and inferential statistical tools were utilized to analyze data collected on a sample size of 321 undergraduate teenage students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Regarding psychological factors, several cross-sectional studies found associations between problematic mobile phone use and loneliness [24,91,98,129,133,158,270,279]. A longitudinal study with 288 participants 13–40 years of age examined causal relations between problematic use, loneliness, face-to-face-interaction, and the need for social assurance [132].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding psychological factors, several cross-sectional studies found associations between problematic mobile phone use and loneliness [24,91,98,129,133,158,270,279]. A longitudinal study with 288 participants 13–40 years of age examined causal relations between problematic use, loneliness, face-to-face-interaction, and the need for social assurance [132].…”
Section: Resultsmentioning
confidence: 99%
“…It was suggested that individuals whose personality trait is easy to feel bored are more possible to indicate Internet addiction ( Chaney and Blalock, 2006 ). Titilope (2014) examined the use of mobile phones from a psychosocial dimension and found that boredom proneness could significantly predict the degree of dependence on mobile phones in adolescents. Leung (2008) found that people who were more likely to be bored used mobile phones more frequently.…”
Section: Introductionmentioning
confidence: 99%
“…1 With the increasing popularity of smartphones, adolescents have developed a strong dependency on them, even bordering on addiction. 2 Consequently, researchers have devoted extensive attention to the issue of smartphone addiction among adolescents. 3 Smartphone addiction refers to the detrimental effects on social function and psychological and behavioral problems caused by excessive reliance and misuse of smartphones.…”
Section: Introductionmentioning
confidence: 99%